2012
DOI: 10.1007/s13314-012-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence reveals presence of Rhizoctonia solani AG 1-IB on Tagetes patula in India

Abstract: Rhizoctonia solani was isolated from marigold (Tagetes patula) showing web blight symptoms in Meghalaya, India. Fluorescence microscopy was used to confirm its multinucleate character. Molecular characterization using ITS1-5.8-ITS2 region of nrDNA proved that it belonged to AG1-IB subgroup. To our knowledge, this is the first record of AG1-IB on marigold from India. Keywords Rhizoctonia solani. Tagetes patula, AG1-IB French marigold (Tagetes patula L.) is an important flower crop grown on commercial scale in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Phylogenetic analysis using maximum parsimony also clustered the isolate with AG 1-IB with 81% bootstrap support (Figure 1). Baiswar et al (2012) have also identified AG 1-IB on soybean and marigold using the primers developed by Matsumoto (2002) and Saylor and Yang (2007). Phylogenetic approach utilizing ITS region has also been used by several workers for accurate identification (Baiswar 2012;Mahendra et al 2016 andSavenai et al 2017).…”
Section: Molecular Identification Of Rhizoctonia Solani Ag 1-ibmentioning
confidence: 99%
“…Phylogenetic analysis using maximum parsimony also clustered the isolate with AG 1-IB with 81% bootstrap support (Figure 1). Baiswar et al (2012) have also identified AG 1-IB on soybean and marigold using the primers developed by Matsumoto (2002) and Saylor and Yang (2007). Phylogenetic approach utilizing ITS region has also been used by several workers for accurate identification (Baiswar 2012;Mahendra et al 2016 andSavenai et al 2017).…”
Section: Molecular Identification Of Rhizoctonia Solani Ag 1-ibmentioning
confidence: 99%
“…Matsumoto (2002) and Saylor and Yang (2007), have designed specifically primed PCR for direct detection of AG 1 and AG 2 subgroups and using these primers, the four isolates SRS, FRS, RSM1 and RSM2 were identified as AG 1 IA. Baiswar et al (2012 and have also identified AG 1-IA on rice and maize, and AG 1 IB on soybean, marigold using the primers developed by Matsumoto (2002) and Saylor and Yang (2007).…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Globally, rice production suffers from various diseases and rice sheath blight is one of the major disease among them. Rhizoctonia solani is a ubiquitous pathogen of rice, vegetables 2 , grains 3 , grasses 4 , etc. causing sheath blight which is the second most devastating disease in rice 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%